Body mass index is superior to other body adiposity indexes in predicting incident hypertension in a highly admixed sample after 10‐year follow‐up: The Baependi Heart Study. Issue 6 (11th May 2022) - Maciel de Oliveira, Camila; França da Rosa, Francielle; de Oliveira Alvim, Rafael; Mourão Junior, Carlos Alberto; Bacells, Mercedes; Liu, Chunyu; Pavani, Jessica; Capasso, Robson; Lavezzo Dias, Fernando Augusto; Eduardo Krieger, José; Costa Pereira, Alexandre
Abstract: Hypertension is the leading cause of overall mortality in low‐ and middle‐income countries. In Brazil, there is paucity of data on the determinants of incident hypertension and related risk factors. We aimed to determine the incidence of hypertension in a sample from the Brazilian population and investigate possible relationships with body adiposity indexes. We assessed risk factors associated with cardiovascular disease, including adiposity body indexes and biochemical analysis, in a sample from the Baependi Heart Study before and after a 10‐year follow‐up. Hypertension was defined by the presence of systolic blood pressure (SBP) ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg or the use of antihypertensive drugs. From an initial sample of 1693 participants, 498 (56% women; mean age 38 ± 13 years) were eligible to be included. The overall hypertension incidence was 24.3% (22.3% in men and 25.6% in women). Persons who developed hypertension had higher prevalence of obesity, higher levels for blood pressure, higher frequency of dyslipidemia, and higher body adiposity indexes at baseline. The best prediction model for incident hypertension includes age, sex, HDL‐c, SBP, and Body Mass Index (BMI) [AUC = 0.823, OR = 1.58 (95% CI 1.23‐2.04)]. BMI was superior in its predictive capacity when compared to Body Adiposity Index (BAI), Body Roundness Index (BRI), and Visceral Adiposity Index (VAI). Incident hypertension in a sample from the Brazilian population was 24.3% after 10‐year follow‐up and BMI, albeit the simpler index to be calculated, is the best anthropometric index to predict incident hypertension.